COMPARATIVE LITERATURE BETWEEN FITZGERALD’S THE GREAT GATSBY AND HAMKA’S TENGGELAMNYA KAPAL VAN DER WIJCK - Falah, A Ilah Nurul; Abbas, Herawaty; P., Amir (JURNAL ILMU BUDAYA, 2020)
This research mainly aimed to find out the similarities and differences in both novels “The Great Gatsby” and “Tenggelamnya Kapal Van Der Wijck”. The data analysis of this research are from both novels which focus on the main characters’ positions.  In analyzing the data, the writer used descriptive comparative method by using Human Models and Heroes of French School in Comparative Literature. The result of this research concluded that the similarities found in main characters’ position, where Gatsby’s position and Zainuddin’s position, they are kind and loyal. They are obsessed on their girl. They are loyal to their own love. While the differences found between Gatsby and Zainuddin are mysterious, fake and religious. Gatsby is a mysterious one while Zainuddin has a clear past description. Gatsby hides his identity and his past to people around him. While Zainuddin is a religious one so that he willing to let Hayati marry to the other man because of his belief in Islam. Zainuddin is the character that has a compassion to people around him.